Health lifestyles of six Zhiguo ethnic groups in China: a latent class analysis - Kaiwen Wu; Jie Chen; Yan Xiao; Chaofang Yan; Xiaoju Li; Yuan Huang; Rui Deng (BMC, 2024)
Abstract Background Zhiguo ethnic groups, commonly known as "the directly-entering-socialism ethnic groups", represent Chinese ethnic minorities who have undergone a unique social development trajectory by transforming directly from primitive societies to the socialist stage. In recent decades, significant lifestyle transformations have occurred among Zhiguo ethnic groups. Understanding their health lifestyles can play a strategic role in China's pursuit of universal health coverage. This study aims to examine patterns of health-related lifestyle among Zhiguo ethnic groups and explore whether sociodemographic features and specific indicators related to health status are associated with particular classes. Methods A cross-sectional study was conducted in Yunnan Province, China, from July to December 2022. Stratified random sampling method was employed to recruit residents belonging to six Zhiguo ethnic groups aged between 15 and 64. Latent class analysis was performed to identify clusters of health-related behaviors within each ethnic group. Logistic regression was utilized to determine the predictors of health lifestyles. Results A total of 1,588 individuals from the Zhiguo ethnic groups participated in this study. Three latent classes representing prevalent health lifestyles among the Zhiguo ethnic groups were identified: "unhealthy lifestyle" (31.80%), "mixed lifestyle" (57.37%), and "healthy lifestyle" (10.83%). In the overall population, individuals belonging to the "healthy lifestyle" group exhibited a higher likelihood of being non-farmers (OR: 2.300, 95% CI: 1.347-3.927), women (OR: 21.459, 95% CI: 13.678-33.667), married individuals (OR: 1.897, 95% CI: 1.146-3.138), and those residing within a walking distance of less than 15 min from the nearest health facility (OR: 2.133, 95% CI: 1.415-3.215). Conversely, individuals in the age cohorts of 30-39 years (OR: 0.277, 95% CI: 0.137-0.558) and 40-49 years (OR: 0.471, 95% CI: 0.232-0.958) showed a decreased likelihood of adopting a healthy lifestyle. Conclusions A considerable proportion of the Zhiguo ethnic groups have not adopted healthy lifestyles. Targeted interventions aimed at improving health outcomes within these communities should prioritize addressing the clustering of unfavorable health behaviors, with particular emphasis on single male farmers aged 30-49, and expanding healthcare coverage for individuals residing more than 15 min away from accessible facilities.